Remote assistance-focused strength training and nutritional guidance in preventing frailty on body composition and muscle strength in community-dwelling Japanese older adults during COVID-19 pandemic - Shiro Izumi; Shino Ujike; Aya Shimosaka; Tomomi Kitajo; Chisato Sawada; Satomi Yamamoto; Kazuhiro Sako; Junko Suzuki (Japanese Society of Physical Fitness and Sports Medicine, 2024)
This study aimed to investigate whether the implementation of a frailty prevention program using remote assistance combined with face-to-face guidance or solely through a remote assistance method is effective for community-dwelling Japanese older adults. Forty-nine community-dwelling older adults (16 men, age: 70.0 ± 4.8 years) were classified into the following three groups: remote plus face-to-face guidance group (RFGG; n = 17), remote guidance group (RGG; n = 17), and control group (CG; n = 15). The RFGG performed face-to-face supervised strength training once a week for the first 4 weeks, plus similar exercises once a week at home, followed by 8 weeks of performing the same exercises twice a week at home while watching an instructional digital versatile disc (DVD) for a total of 12 weeks. They received one face-to-face nutritional guidance session, followed by guidance over the telephone once a month for 3 months. The RGG performed the same exercises at home while watching the DVD twice weekly and received nutritional guidance over the telephone once a month for 3 months (12 weeks). Only pre- and post-intervention surveys in the CG were conducted. When compared to pre-intervention measurements, RFGG lean body mass, lower limb muscle mass, and grip strength increased significantly, while fat mass percentage decreased significantly (p < 0.05). In the RGG, no significant changes were observed in the physical characteristics. These results suggest that a frailty prevention program not only using a remote guidance but also combined with a face-to-face guidance may be effective for older adults.